Managing Retirement Risk in an Ageing World: The Global Picture - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
According to HSBC’s 2007 global retirement study, most retirees in their 60s and 70s are living healthy, happy and productive lives. However, as the world rapidly ages, most pre-retirees are surprisingly unconcerned about how they will cope in their retirement. In Part 1 of a 2-part article, Olivia Mitchell, Wharton professor of insurance and risk management, who is also a chaired professor at Singapore Management University, cautions that these people might be living with a false sense of security, and could face a rude awakening when it is too late to do anything about it.